1989
DOI: 10.1080/02626668909491373
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the greenhouse effect on sewerage systems—Lund case study

Abstract: The possible impacts of modifications in rainfall patterns due to the greenhouse effect on the function of a sewerage system are studied based on a case study of the city of Lund, Sweden. The Storm Water Management Model is used to simulate changes in the runoff pattern. The paper lists the possible effects of increases in rainfall intensity on the urban water cycle, quantifies changes in the runoff pattern, and discusses the significance of detected changes in terms of economic and environmental consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…For Lund, although the storm water system is designed to accommodate further development of the city, increased rainfall intensity of 20-30 % would result in significant flooding problems for the city's sewage network (Niemczynowicz 1989). Semadeni-Davies et al (2008b) showed that for Helsingborg, the impacts of urbanisation and climate change could be more than met by implementing current developments in urban water management.…”
Section: Wastewater Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…For Lund, although the storm water system is designed to accommodate further development of the city, increased rainfall intensity of 20-30 % would result in significant flooding problems for the city's sewage network (Niemczynowicz 1989). Semadeni-Davies et al (2008b) showed that for Helsingborg, the impacts of urbanisation and climate change could be more than met by implementing current developments in urban water management.…”
Section: Wastewater Managementmentioning
confidence: 99%
“…Consequently, urban areas, which are characterised by fewer storage elements than rural basins, would respond with further decreases in storage capacity and enhanced run-off (Niemczynowicz 1989). The impacts of changing precipitation patterns on drainage and sewage systems have mainly been assessed by studies using hydrological modelling systems with various assumptions about future precipitation amount (Niemczynowicz 1989;Semadeni-Davies et al 2008a, b;Nie et al 2009). The modelling studies usually use climate scenarios based on different global and regional climate model results (Semadeni-Davies et al 2008a, b;Olsson et al 2009).…”
Section: Wastewater Managementmentioning
confidence: 99%
See 3 more Smart Citations